Efectos comportamentales y moleculares del estrés agudo, etanol y la cafeína en el pez Cebra (2021)
Stress is a risk factor for several organic diseases including psychiatric disorders such as anxiety, depression, and substances use disorders, among others. Alcohol is a widely used substance in the world and its acute effects on a behavioral level are known. The effect of environmental stress and substances on behavior has been studied separately. Short and long-term stress in zebrafish can generate alterations in the CNS affecting anxiety levels in different behavioral tests such as locomotion, social, learning and memory behavior. However, in the brain, the molecular effects of environmental stress are poorly understood in association with alcohol and other substances such as caffeine, consumed throughout the world.